The weaker contracting party (Determination of legal category) - Alejandro Ossola, Federico (2007)
In the present study, the author focuses his attention on one of the legal categories that have worried the civilest the most , in attention to that, the defense and protection of the consumers and users constitute one of the capital subjects and more deep importance in the present process of transformation of the patrimonial Private Law: the figure of the weak contractor. In it, one studies concerning the origin of the expression, his real sense, as well as the its determination as objective category is analyzed referring to or of appreciation in concrete; all it stops to derive in conclusions that help to outline their correct interpretation.